2006
DOI: 10.1038/sj.cdd.4401876
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions remain open during cytochrome c-induced cell death: relationship of conductance to ‘bystander’ cell killing

Abstract: Previous reports have shown that gap junctions relay cell death in many cell types. However, changes in electrical coupling and their dynamics during cell death are poorly understood. We performed comprehensive studies of electrical coupling following induction of cell death by single-cell cytochrome c (cyC) injection in paired Xenopus oocytes. Cell death was rapidly induced by cyC in injected cells, and cell death was also observed in uninjected bystander cells electrically coupled to the cyC-injected oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…It is of particular interest that cell death caused in developing neurons by NMDA receptor hypofunction is dependent on Bax/cytochrome c apoptotic mechanisms (de Rivero Vaccari et al 2006), whereas NMDA receptordependent excitotoxicity has been reported to be dependent on poly(ADP-ribose) polymerase and free-radical mechanisms, and may be Bax independent (Yu et al 2003). Findings on baby hamster kidney cells and on Xenopus oocytes suggest that gap junctions play a role in propagation of death signals mediated by cytochrome c (Udawatte and Ripps 2005) and that inositol triphosphate (IP 3 ) and Ca 2ϩ likely serve as such gap junction-permeable signals (Cusato et al 2006). Additionally, it has been suggested that Na ϩ , Ca 2ϩ , and IP 3 are generated during NMDA receptor-dependent excitotoxicity and serve as gap junction-permeable death signals during ischemia and traumatic injury (Frantseva et al 2002a,b).…”
Section: What Is the Nature Of Neurodegenerative Signals?mentioning
confidence: 92%
See 1 more Smart Citation
“…It is of particular interest that cell death caused in developing neurons by NMDA receptor hypofunction is dependent on Bax/cytochrome c apoptotic mechanisms (de Rivero Vaccari et al 2006), whereas NMDA receptordependent excitotoxicity has been reported to be dependent on poly(ADP-ribose) polymerase and free-radical mechanisms, and may be Bax independent (Yu et al 2003). Findings on baby hamster kidney cells and on Xenopus oocytes suggest that gap junctions play a role in propagation of death signals mediated by cytochrome c (Udawatte and Ripps 2005) and that inositol triphosphate (IP 3 ) and Ca 2ϩ likely serve as such gap junction-permeable signals (Cusato et al 2006). Additionally, it has been suggested that Na ϩ , Ca 2ϩ , and IP 3 are generated during NMDA receptor-dependent excitotoxicity and serve as gap junction-permeable death signals during ischemia and traumatic injury (Frantseva et al 2002a,b).…”
Section: What Is the Nature Of Neurodegenerative Signals?mentioning
confidence: 92%
“…Some reports indicate that blocking gap junctions during development, ischemia, or traumatic brain injury rescues cells from apoptosis or necrosis, suggesting that gap junctions contribute to neural cell death (Cusato et al 2003(Cusato et al , 2006de Pina-Benabou et al 2005;Frantseva et al 2002a,b;Nodin et al 2005;Perez Velazquez et al 2006;Rami et al 2001;Rawanduzy et al 1997;Udawatte and Ripps 2005); others demonstrate that gap junctions are neuroprotective (Blanc et al 1998;Nakase et al 2003;Oguro et al 2001;Ozog et al 2002;Siushansian et al 2001;Striedinger et al 2005). Apparently, gap junctions may contribute to both neurodegeneration and neuroprotection depending on the type of connexins, cells coupled, region of the nervous system, stage of development, type of injury, and other factors.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…We triggered apoptosis by loading the cells using in situ electroporation with cytochrome C (cytC), a signaling agent located far downstream in the intrinsic apoptotic pathway, 21 thereby avoiding upstream signaling events that may complicate the picture. Earlier studies with cytC-triggered apoptosis provided evidence for a role of direct cell-to-cell communication through GJs in the spread of cell death, 1,[22][23][24] but none of these studies have focussed on the role of hemichannels in the communication of cell death. Our data obtained in C6 glioma cells stably transfected with Cx43 (C6Cx43), using various Cx channel-inhibiting approaches including post-transcriptional Cx43 gene silencing, suggest that GJs contribute to the spread of apoptosis to directly neighboring bystander cells whereas hemichannels promote apoptosis in regions located as far as several 100 mm away from the initial cytC-loaded cell zone.…”
mentioning
confidence: 99%
“…The BE allows these drugs or their signaling intermediates to reach by diffusion more cells than they would do alone (Peixoto et al 2009) (Jensen and Glazer 2004;Udawatte and Ripps 2005). In fact, it has been shown that gap junctions remain open during the apoptotic process (Cusato et al 2006). However, there are additional, less understood mechanisms for the role of gap junctions in BE cytotoxicity.…”
Section: Role Of Apoptosis In the Bystander Effect Cytotoxicitymentioning
confidence: 99%